Modelagem matemática e interconexões com tecnologias na educação básica brasileira - AMARAL, Mauro Laureno do (2023)
This research will discuss the use of Mathematical Modeling and Technologies in Brazilian Basic Education. This theme is of fundamental importance, since research and discussions about the possibilities that teaching modeling linked to ICTs can bring become more and more frequent. The importance of this research is justified to understand the strategies used by teachers who work in Brazilian basic education and how they link mathematical modeling and technologies in their practices, since this application can bring many benefits to students. The work was developed through the following problem: How can mathematical modeling and technologies help in the development of students, and how is this tool used in the classroom? Therefore, the general objective of this research is to investigate the use and application of mathematical modeling and technologies in the teaching and learning process of mathematical modeling. Data analysis indicated that the research achieved the proposed objectives, according to the information obtained, we identified that the use of modeling and technologies can significantly improve the teaching and learning process.